ANALISIS KINERJA DENGAN METODE ECONOMIC VALUE ADDED (EVA ) DAN FINANCIAL DISTRESS SUATU STUDI PADA PT BANK UMUM SYARIAH - Liviawati Liviawati; Gusmarila Eka Putri (Jurnal Akuntansi Kompetif, 2026)
Bank Muamalat is the first Islamic bank in Indonesia. The government once planned its acquisition through Bank BTN, but the plan was canceled after due diligence results. Bank Syariah Indonesia (BSI) was formed from the merger of BRI Syariah, BNI Syariah, and Mandiri Syariah due to declining performance in some entities. Analysis shows that Bank Muamalat’s performance has weakened, with a capital structure dominated by debt. Its Debt-to-Equity Ratio indicates debt is ten times higher than equity, and over 90% of its assets are financed by liabilities, suggesting high financial risk despite appearing stable to customers. This study examines performance using EVA and financial distress in Islamic banks in Indonesia. Results show that in 2021, three banks failed to generate economic value added, but by 2023–2024 all sampled banks succeeded. However, several banks, including Bank Muamalat and others, consistently experienced financial distress during 2021–2024